(untitled) - Zemansky, Mark W (New York, 1997)
Contents: Fudamental concepts; simple thermodynamics systems; heat and the first law of thermodynamics; the second law of thermodynamics.
Nguyên lý các quá trình chế biến thực phẩm
Keywords: Heat,Thermodynamics